Diamond-coated 'black silicon' as a promising material for high-surface-area electrochemical electrodes and antibacterial surfaces. Issue 34 (12th August 2016) - May, P. W.; Clegg, M.; Silva, T. A.; Zanin, H.; Fatibello-Filho, O.; Celorrio, V.; Fermin, D. J.; Welch, C. C.; Hazell, G.; Fisher, L.; Nobbs, A.; Su, B.
Abstract : Coating black silicon needles in a uniform layer of conducting boron-doped CVD diamond produces a high-surface-area electrode material that promising for electrochemical applications, as well as acting as a robust bactericidal surface. Abstract : This report describes a method to fabricate high-surface-area boron-doped diamond (BDD) electrodes using so-called 'black silicon' (bSi) as a substrate. This is a synthetic nanostructured material that contains high-aspect-ratio nano-protrusions, such as spikes or needles, on the Si surface produced via plasma etching. We now show that coating a bSi surface composed of 15 μm-high needles conformably with BDD produces a robust electrochemical electrode with high sensitivity and high electroactive area. A clinically relevant demonstration of the efficacy of these electrodes is shown by measuring their sensitivity for detection of dopamine (DA) in the presence of an excess of uric acid (UA). Finally, the nanostructured surface of bSi has recently been found to generate a mechanical bactericidal effect, killing both Gram-negative and Gram-positive bacteria at high rates. We will show that BDD-coated bSi also acts as an effective antibacterial surface, with the added advantage that being diamond-coated it is far more robust and less likely to become damaged than Si.